Mitochondrial DNA Haplogroup M7 Confers Disability in a Chinese Aging Population - Sun, Dayan; Yao, Shun; Wu, Fei; Deng, Wan; Ma, Yanyun; Jin, Li; Wang, Jiucun; Wang, Xiaofeng (Frontiers in Genetics, 2020)
Mitochondrial DNA (mtDNA) haplogroups have been associated with functional impairments (i.e., decreased gait speed and grip strength, frailty), which are risk factors of disability. However, the association between mtDNA haplogroups and ADL disability is still unclear. In this study, we conducted an investigation of 25 mtSNPs defining 17 major mtDNA haplogroups for ADL disability in an aging Chinese population. We found that mtDNA haplogroup M7 was associated with an increased risk of disability (OR = 3.18 [95% CI = 1.29–7.83], P = 0.012). The survival rate of the M7 haplogroup group (6.1%) was lower than that of the non-M7 haplogroup group (9.5%) after a six-year follow-up. In cellular studies, cytoplasmic hybrid (cybrid) cells with the M7 haplogroup showed distinct mitochondrial functions from the M8 haplogroup. Specifically, the respiratory chain complex capacity was significantly lower in M7 haplogroup cybrids than in M8 haplogroup cybrids. Furthermore, an obvious decreased mitochondrial membrane potential and 40% reduced ATP-linked oxygen consumption were found in M7 haplogroup cybrids compared to M8 haplogroup cybrids. Notably, M7 haplogroup cybrids generated more reactive oxygen species (ROS) than M8 haplogroup cybrids. Therefore, the M7 haplogroup may contribute to the risk of disability via altering mitochondrial function to some extent, leading to decreased oxygen consumption, but increased ROS production, which may activate mitochondrial retrograde signaling pathways to impair cellular and tissue function.